Entre os domínios da metáfora e da metonímia na produção de sentido em charges animadas - Natália Elvira Sperandio (2014)
In this dissertation, I raise, as a research problem, the interaction of metaphorical and metonymic processes in the production of meaning in multimodal texts. My proposal is to explain in detail the way metaphor and metonymy are articulated in the production of meaning beyond the verbal level. In order to do so, I expand my investigation to different semiotic modes present in the construction of the so-called multimodal texts. For this purpose, I present the main works devoted to these processes, showing the path from the classical perspective to cognitive studies. My methodological horizon is based on the Conceptual Metaphor Theory (LAKOFF; JOHNSON, 1980, 1999, 2003), used in the conceptualization of the metaphorical phenomenon, together with the Conceptual Blending Theory (FAUCONNIER; TURNER, 2002), and the Multimodal Metaphor proposal (FORCEVILLE, 1996, 2008, 2009). This theoretical articulation is justified by the creative metaphors - which are built by various semiotic modes - contemplated in the analyses. The theoretical perspective of Kövecses and Radden (1999) was adopted in conjunction with Jakobsons (1956, 2003) and Paivas (2010, 2011, 2012) studies on the approach to the metonymic phenomenon. This theoretical association is made so as to promote a more comprehensive study of this phenomenon. Besides, I also refer to works related to the interaction of these processes, such as the pioneering studies conducted by Goossens (2003), Barcelona (2003) and Radden (2003). Extending this theoretical framework, I introduce the works of Fauconnier and Turner (1999, 2002) and Paiva (2010, 2011, 2012) on metaphorical/metonymic interaction. Thus, I establish strategies which allow me to identify and analyze metaphors, metonymies and their interactions in my corpus - animated cartoons produced by the cartoonist Maurício Ricardo. As a result, I set out how metaphorical and metonymic domains interact with one another in order to produce meaning in a multimodal text. In my analyses, I demonstrate that every metaphor is motivated by a complex set of metonymies that are created by the relations of the elements in the input spaces (which served as the source and the target domains of the metaphor in question). In this sense, activation, deployment and mapping intra-domain will happen before the inter-domain mapping, characterizing the relationship between the elements of these spaces as metonymic associations. I note that this interaction occurs simultaneously. In this sense, the metaphor is the result of this complex set of metonymies. This fact demonstrates the importance of the metonymic process in the creation of the metaphorical process. Finally, I highlight the role of different semiotic modes in this interaction. These semiotic modes introduce new elements in the production of metaphors and metonymies, making the interaction between them more complex.